REPRESENTASI CITRA DIRI LAKI-LAKI DALAM IKLAN (Studi Pada Iklan Rokok U-Mild) - Sutriya, Boy; Alit Suryawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2019)
ABSTRACT Advertising these days has been the inseparable part from media massa whether it is print media, electronic media and internet media as new media. Advertising is designed to create certain tastes to comodity or product, and that is what the ads of ‘rokok u-mild versi cowo tau kapan harus bohong’ trying to tell. in this advertisement, the director is tried to describe how do you represent of male self-image. The goal of this study is to find out the represent of self image that is shown in cigarette advertisements, with qualitative descriptive methods approach and Roland Barthes semiotic analysis methods. The result of this study showing masculine self-image but also understanding women’s feeling.   Keywords: Advertising, U-Mild Cowo Tau Kapan Harus Bohong, Representation of MaleSelf-image, Semiotics